Distribution of neuroendocrine cells in the small and large intestines of the mole-rats (Spalax leucodon) - Bayrakdar, Ali; Yaman, Mine; Ilgun, Ramazan (Taylor & Francis Ltd, 2015)
In this research, we aimed to determine the regional distribution and relative frequency of immunoreactive (IR) endocrine cells of ghrelin, glucagon, somatostatin-14 (SOM-14), neuropeptide Y (NPY), calcitonin-gene-related peptide (CGRP), insulin and galanin in small and large intestines of mole-rats (Spalax leucodon) by using immunohistochemical staining methods. For this purpose, small and large intestine regions of six adult mole-rats were used as material. In the small and large intestines of mole-rats (S. leucodon), ghrelin, glucagon, SOM-14, NPY and CGRP were identified at various frequencies, but insulin and galanin were not detected in this study. Ghrelin-IR cells were only observed in the small intestine. In addition, the existence of positive staining in the cells was decreased while passing from duodenum to ileum. Glucagon-IR cells were mainly detected in the small intestine regions and colon. SOM-14-IR cells were detected throughout the small intestines with a lesser frequency. NPY-IR cells were also detected in the small and large intestines at various frequencies but not in cecum and rectum. CGRP-IR cells were scarce in duodenum and jejunum, but their numbers increased from ileum to colon. In conclusion, the present study revealed the existence and distributions of neuropeptide-secreting endocrine cells in small and large intestines of mole-rats (S. leucodon).
Keywords: Mole-rats (Spalax leucodon); gastrointestinal tract; immunohistochemistry